Pembangunan modul pembelajaran seni reka grafik berasaskan teknologi dan gaya pembelajaran pelajar bermasalah pendengaran / Zainuddin Ibrahim - Zainuddin, Ibrahim (2017)
This study was aimed to developing a graphic design learning module based on technology and hearing-impaired student learning styles. The Design and Development Research methodology introduced by Richey and Klein (2007) involving three phases was used in this study. Data from the first phase, the needs analysis, were collected through questionnaires administered on 58 hearing-impaired students in Special Vocational Secondary School and Polytechnic, while semi-structured interviewed were conducted on five academic instructors in graphic design and hearing-impaired field using purposive sampling method. Findings from the closed-ended questions were analyzed by descriptive statistic while the open-ended responses were subjected to thematic analysis. The data from the second phase were obtained through the Fuzzy Delphi technique of 24 experts in special education, education technology, curriculum and graphic design fields. Analysis relied on the experts’ responses to the questionnaire based on a five-point Fuzzy Linguistic Likert Scale. The threshold ‘d’ value was calculated to determine the experts’ consensus on all questionnaire items. The phase two of development involved refinement of lesson plans and web designs with the “Introduction of Graphic Animation, Graphic Animation Framework, Graphic Animation Composition, Graphic Animation Creation and Graphic Animation Documentation” topics. The phase three, the effectiveness testing, was conducted using pretest and posttest on students’ knowledge while post-test on graphic animation skills project were assessed on 15 hearing-impaired students. Furthermore, usability testing was done through retrospective on 10 hearing-impaired students who had used the graphic design learning module with one interpreter. Semi structured interview responses were analyzed thematically. The findings show that there was a need to develop a graphic design module for hearing-impaired based on technology and learning styles. The majority of the students agreed that graphic animation is most difficult course compared to others. In addition, index learning styles score indicated that hearing-impaired students have different learning styles. According to the academicians, learning module based on student-impaired learning style was yet to be implemented and thus, these findings supported the relevance of graphic design module development for the hearing-impaired students. The findings in the phase two of design study showed that the experts achieved unanimous consensus with the threshold ‘d’ value ≤ 0.2, exceeded 75% for the suitability of item in the learning module. The findings of the development phase suggested the needs of improvement especially on the video quality recorded. Paired Sample t Test and One Sample t Test showed significant improvement on knowledge and skill achievement with p value .000 which less than .05 (p < .05). Results from the usability testing proved that the students gained new experiences such as learning the topic swiftly, learning through own styles of learning, comprehensive and enjoyable. The proposed module is relevant for the Ministry of Education, Ministry of Higher Education and Academicians in graphic design fields.